The Effect of Realistic Mathematics Education Implementation in Mathematics Learning in Elementary School - Samritin Samritin; Siti Rahmalia Natsir; Abdul Manaf; Eka Rosmitha Sari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2023)
Until now, mathematics is still a difficult subject for students. This is one of the implications of the abstract nature of mathematics. For this reason, mathematics learning is designed in such a way by bringing mathematics closer to the real-life context and student experience. Realistic Mathematics Education (RME) is an alternative learning approach that is able to reduce the gap between abstract mathematics and real life. This research was conducted using a quasi-experimental method that aims to test the effectiveness of RME in mathematics learning in elementary schools. The study used one group pretest-post test design. A study sample of N = 19 was selected from class V of SD Negeri 2 Labalawa, Baubau City. Data analysis was performed using descriptive statistics and non-parametric inferential statistics. The results showed that the average gain score of pretests and post-tests reached 44.09 with a Standard Error of Mean of 3,763 and 4,811, respectively. The test results of the average difference between the pretest and post-test were declared significant at a confidence level of 95% or ?=0.05. The indication is indicated by a Mann-Whitney test value of 23,000 with a2-tailed asymptotic fiancy value of 0.000 < 0.05. The results of the data analysis of this study concluded that the implementation of RME has a significant effect on mathematics learning outcomes in elementary schools. The results of this study have positive implications for changing the teaching style and learning style of students from teacher oriented to students oriented.